How to Protect and Promote the Nutrition of Mothers and Children in Latin America and the Caribbean : Priority Nutrition Interventions and Cross-Cutting Approaches - World Bank (World Bank, Washington, DC, 2016)
This section describes the priority nutrition interventions and cross-cutting approaches that are essential to promote and protect the nutritional status of mothers and children as well as a country's human capital in the short-, medium-, and long-terms. The main thrust of the guidance is that: (1) policies give special attention to the critical 'window of opportunity' represented by the first 1,000 days of life; (2) policies are aligned with the latest international recommendations in nutrition; (3) policies and interventions of key sectors are coordinated to provide synergy of action; and (4) resources allocated for disaster prevention and emergency management are invested in the most cost-effective way. Monitoring is a continuous process of collecting and analyzing information to better understand how well a program is operating against expected outputs and to allow remedial intervention to correct failures. Situation monitoring measures the change or lack of change, in a condition or a set of conditions and includes monitoring of the wider context. Performance monitoring, on the other hand, measures progress in achieving specific results in relation to an implementation plan. Evaluation is a systematic and objective assessment that attempts to determine the worth or significance of an intervention, strategy, or policy. It is used to appraise the effectiveness of an intervention to determine if it meets its goals, to estimate its results or impact, and to identify its costs vs. its benefits. Promote optimal breastfeeding practices. Provide all pregnant women with daily iron-folic acid supplements for at least six months. Provide deforming treatment to pregnant women, preschool-aged children, and school-aged children in areas where hookworms or soil-transmitted helminthes are prevalent. Establish strong links between agricultural, food security, social protection and nutrition policies that can be used to inform a robust communication program regarding maternal diet and critical infant and young child feeding practices. Support diversified agricultural production to increase availability of nutrient-dense foods, particularly those of animal sources.